A Comparison between Enriched and Nonenriched Enrollment Randomized Withdrawal Trials of Opioids for Chronic Noncancer Pain - Andrea D Furlan; Luis E Chaparro; Emma Irvin; Angela Mailis-Gagnon (Pain Research and Management)
An enriched enrollment randomized withdrawal (EERW) trial design has been advocated to be useful for the study of drugs that are beneficial to only a fraction of the individuals who take them. Some investigators defend the use of enrichment designs for opioids in chronic noncancer pain (CNCP), reasoning that opioids may appear to underperform in clinically heterogeneous contexts, ie, that substantial efficacy in a particular patient subgroup may be diluted or masked by poor efficacy in another subgroup. The authors previously published a systematic review of opioids for CNCP in 2006; however, at that time, there were only a few EERW trials available for comparison. This more exhaustive, updated review compares the results between EERW and non-EERW trials of opioids for a variety of CNCP conditions.